Rancang Bangun Aplikasi Penitipan Hewan Peliharaan Berbasis Android - Evan Tanuwijaya (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
A lot of people in Indonesia keeps their pets at their home. Therefore, the pets must be taken care at all time. But we as humans have many other activities besides taking care of our pets. This causes the pet not to be monitored. To solve the problem, an app is required to search for a pet daycare. This app can search for healthy, comfortable, and safe pet daycare. Applications have been widely developed in the community, especially for mobile applications. Mobile applications have many advantages and ease in accessing them. In addition, in Indonesia technology is growing very fast. Many Indonesians are also using smartphones in their daily lives. Based on the above data, a solution appears to create an app for pet daycare where pet owners can easily search for pet daycare just with their smartphones. This app uses a client-server architecture where the client is a smartphone that has an Android operating system and a server using Google Firebase. Development method used is the Systems Development Life Cycle (SDLC) method with the Waterfall model. The result of this thesis, it can be concluded that Petqper mobile application can look for healthy, convenient, and safe daycare. In addition, reliable pet daycare can use this application to offer their services and simplify the process of booking a place.